Creating deviance: an interactionist approach - Dotter, Daniel L. (Altamira Press, 2004)
Social deviance, the interactionist tradition, and cultural studies -- The scenario as interpretive strategy : an interactionist/cultural studies articulation -- Reading interactionism : pragmatism and the problem of meaning -- The creation of deviance : social definition and the process of interaction -- Toward a postmodern cultural studies : meaning creation in media culture -- Rock in a hard place : historical stigmatization of adolescent subcultures in popular music -- Murder in the media : cultural criminology, constructions of violence, and a crime of the early century -- Theorizing deviance in the postmodern : the turn continues